Wear of UHMWPE against nitrogen-ion-implanted and NbN-coated Co-Cr-Mo alloy formed by plasma immersion ion implantation and deposition for artificial joints - Park, Won-Woong; Kim, Eun-Kyeom; Jeon, Jun-Hong; Choi, Jin-Young; Moon, Sun-Woo; Lim, Sang-Ho; Han, Seung-Hee (ELSEVIER, 2012)
NbN thin film was deposited on the Co-Cr-Mo alloy by plasma immersion ion implantation and deposition (PIII&D) to reduce the volume wear rate of UHMWPE. In addition, nitrogen ions were implanted on the surface of the Co-Cr-Mo alloy prior to the NbN film deposition in order to increase the hardness of the substrate. XPS analysis revealed that nitrogen ions were implanted into the surface of the Co-Cr-Mo alloy, leading to the formation of CrN and Cr2N. The UHMWPE volume wear rate was measured using a pin-on-disk tribometer. The wear test result showed that the volume wear rate of UHMWPE against NbN-coated Co-Cr-Mo alloy declined by 20% as compared to that in the untreated Co-Cr-Mo alloy. In addition, the UHMWPE wear rate against the nitrogen-ion-implanted and NbN-coated Co-Cr-Mo alloy could be drastically reduced by up to 48%. It can be concluded that a combination of prior nitrogen ion implantation and NbN coating via PIII&D is a promising surface treatment tool for extending the lifetime of metal-on-polymer artificial joints. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: MOLECULAR-WEIGHT POLYETHYLENE; TRIBOLOGICAL CHARACTERIZATION; COBALT-CHROMIUM; COATINGS; BEHAVIOR